2019
DOI: 10.4103/jmas.jmas_196_17
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopically assisted insertion of peritoneal dialysis catheter

Abstract: Peritoneal dialysis (PD) is a generally accepted method for treatment of patients with the end-stage renal disease. A larger proportion of PD patients transfer to haemodialysis every year than the converse. Many of the underlying causes of transfer to haemodialysis are preventable. Infectious complications still remain the most common reason for transfer of PD patients to haemodialysis, catheter-related problems are the second most common cause. For PD to be effective it is very important to provide a quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…A study by Chou et al, 2019, also showed increasing in the incidence of ESRD in elderly patients with CKD [36]. The laparoscope process shown a minimal invasive, more acceptable, and higher safety profile in addition to better outcome and less incidence of catheter obstruction and change in comparison with the open operation, accordingly, there is a universal orientation toward laparoscope PD operations [39], [40]. This reflects the large number of patients with laparoscope PD in the current study and clinicians preference of laparoscopic over open CAPD in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…A study by Chou et al, 2019, also showed increasing in the incidence of ESRD in elderly patients with CKD [36]. The laparoscope process shown a minimal invasive, more acceptable, and higher safety profile in addition to better outcome and less incidence of catheter obstruction and change in comparison with the open operation, accordingly, there is a universal orientation toward laparoscope PD operations [39], [40]. This reflects the large number of patients with laparoscope PD in the current study and clinicians preference of laparoscopic over open CAPD in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…With the development of minimally invasive and laparoscopic surgery, laparoscopic PDC insertion is becoming widely accepted with minor complications and better outcomes [ 9 ]. Laparoscopic PDC insertion techniques can be divided into basic laparoscopic techniques and advanced laparoscopic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience we have used soft silicone catheters, with a multi-hole pig-tail distal end to be placed in the Douglas cul-de-sac and a proximal end with two Dacron® cuffs one of which is placed in the preperitoneal space and the other in the subcutaneous space. (1)(2)(3)(4)(5) We placed the catheter on the right side of the abdomen to accommodate the peristalsis; the peristalsis results in clockwise movement of the ileal loops so a left-sided catheter could be easily displaced…”
Section: Surgical Techniquementioning
confidence: 99%
“…Patients are discharged safely on the rst postoperative day. (1)(2)(3)(4)(5)(6)(7) The nephrologist is responsible for catheter management and break-in to peritoneal dialysis.…”
Section: Surgical Techniquementioning
confidence: 99%